Cover Image, Volume 7, Issue 1. (March 2016) - Unknown
Abstract : The cover photograph is a glass goblet from the Sassanid (Neo‐Persian) Empire with typical surface iridescence alteration. Discovered in the Neyshabur, Khorasan Province, (the discovery date is unknown), the goblet is thought to have been made around 350 AD. The photograph was provided courtesy the private collection of the late Iranian monarchy (Pahlavi Dynasty), located in the Archaeological Museum of Niavaran Palace, Tehran, Iran. For further details, see "Iridescence in Ancient Glass: A Morphological and Chemical Investigation, " this issue. Abstract : The cover photograph is a glass goblet from the Sassanid (Neo‐Persian) Empire with typical surface iridescence alteration. Discovered in the Neyshabur, Khorasan Province, (the discovery date is unknown), the goblet is thought to have been made around 350 AD. The photograph was provided courtesy the private collection of the late Iranian monarchy (Pahlavi Dynasty), located in the Archaeological Museum of Niavaran Palace, Tehran, Iran. For further details, see "Iridescence in Ancient Glass: A Morphological and Chemical Investigation, " this issue.